2022
DOI: 10.3390/su142215362
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zero Growth of Fertilizer Action on Ecological Efficiency of Grain Production in China under the Background of Carbon Emission Reduction

Abstract: At present, the problem of non-point source pollution and carbon emissions caused by excessive application of fertilizer is increasingly serious and has caused damage to the ecological environment. The “zero growth of fertilizer use by 2020 action plan” was introduced to solve the related ecological and environmental problems. Based on the panel data of 31 provinces in China from 1998 to 2020, this paper used the super efficiency SBM model to measure the ecological efficiency of grain production in China, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Education can improve farmers' application of technology and improve productivity, which is consistent with the research of M. Reimers, Wu Y., and others [51,52]. Through education and training, farmers have improved their production skills and awareness of environmental protection, thus improving the efficiency of input factors and reducing the use of polluting production factors such as chemical fertilizers and pesticides, which is conducive to improving AEE [22,26]. The difference is that both HHC and MHC also have a significant promotional effect on AEE.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Education can improve farmers' application of technology and improve productivity, which is consistent with the research of M. Reimers, Wu Y., and others [51,52]. Through education and training, farmers have improved their production skills and awareness of environmental protection, thus improving the efficiency of input factors and reducing the use of polluting production factors such as chemical fertilizers and pesticides, which is conducive to improving AEE [22,26]. The difference is that both HHC and MHC also have a significant promotional effect on AEE.…”
Section: Discussionsupporting
confidence: 81%
“…By educating and training farmers, their production ideas, knowledge and skills, and awareness of environmental protection will be affected, which will change their production decisions and further affect AEE. On the one hand, farmers can not only effectively improve the efficiency of technology use but also enhance their ability to absorb new technologies and knowledge by receiving vocational education and technical training [22]. This has also been proven in other regions.…”
Section: The Role Of Educational Human Capitalmentioning
confidence: 99%
“…Government policies can have a significant impact on multi-crop N fertilizer management in agriculture. Comparing the data on agricultural fertilizer use in Hubei Province for the last 10 years [46], we found that the implementation of the zero growth in fertilizer use policy effectively reduced the amount of fertilizer applied and reduced fertilizer nonpoint source pollution and carbon emissions, which improved the ecological efficiency of food production [47]. This phenomenon indicates that the policy also played a role in the reduction in N fertilizer application.…”
Section: Influence Factors Of Multi-crop N Fertilizer Managementmentioning
confidence: 86%
“…Correspondingly, China is the world's largest producer and consumer of fertilizers [2]. Fertilizer application in China is 328.5 kg per hectare, far exceeding the global average of 120 kg per hectare [3]. This excessive use of fertilizer has resulted in various non-point source pollution issues, such as soil compaction [4], the eutrophication of water bodies [5], and heavy metal contamination of the soil [6].…”
Section: Introductionmentioning
confidence: 99%